2018
DOI: 10.1016/j.neuron.2018.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Robustness to Temperature Perturbation Is Altered by Neuromodulators

Abstract: SUMMARY In the ocean, the crab, Cancer borealis, is subject to daily and seasonal temperature changes. Previous work, done in the presence of descending modulatory inputs, had shown that the pyloric rhythm of the crab increases in frequency as temperature increases, but maintains its characteristic phase relationships until it “crashes” at extreme high temperatures. To study the interaction between neuromodulators and temperature perturbations, we studied the effects of temperature on preparations from which t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 107 publications
(150 reference statements)
7
70
1
Order By: Relevance
“…In this work, we build on the results in Caplan et al, 2014 and implemented temperature sensitivity in a model of the pyloric network ( Prinz et al, 2004 ). We show that in these models, there are multiple sets of maximal conductances and temperature sensitivities that reproduce much of the experimental phenomenology previously reported ( Tang et al, 2010 ; Tang et al, 2012 ; Soofi et al, 2014 ; Haddad and Marder, 2018 ). In addition, we explored how the dynamics of the currents are modified to sustain the correct activity at each temperature.…”
Section: Introductionsupporting
confidence: 79%
See 3 more Smart Citations
“…In this work, we build on the results in Caplan et al, 2014 and implemented temperature sensitivity in a model of the pyloric network ( Prinz et al, 2004 ). We show that in these models, there are multiple sets of maximal conductances and temperature sensitivities that reproduce much of the experimental phenomenology previously reported ( Tang et al, 2010 ; Tang et al, 2012 ; Soofi et al, 2014 ; Haddad and Marder, 2018 ). In addition, we explored how the dynamics of the currents are modified to sustain the correct activity at each temperature.…”
Section: Introductionsupporting
confidence: 79%
“…Because the contribution of a given current to a neuronal process can be replaced by another at different temperatures, deletion or blockade of a current can produce qualitatively different effects at high and low temperatures. These results provide a plausible hypothesis for why interactions between temperature and a second perturbation can be observed experimentally ( Haddad and Marder, 2018 ; Ratliff et al, 2018 ).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…The concept has been nicely illustrated by Eve Marder's group . They showed that different animals respond differently to the same external challenge . The biological disparities between animals constrain the form of the response.…”
Section: In Diversity We Learnmentioning
confidence: 99%